2017
DOI: 10.2214/ajr.16.17285
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative 3-T Proton MR Spectroscopy for the Characterization of Musculoskeletal Neoplasms: Update on Diagnostic Performance and Indications

Abstract: Qualitative 3-T H-MRS cannot be used to characterize bone tumors. This technique has good sensitivity but poor specificity for the characterization of soft-tissue lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…MRS is a technique that is used to noninvasively detect and distinguish metabolite activity in a tissue of interest, such as a soft tissue tumor, based on the intrinsic resonant frequencies of various metabolites, and analyze its biochemical composition . MRS enables the detection of metabolic markers of malignancy, including the trimethyl aluminium (TMA) compounds, which present as a composite spectral resonance consisting of free choline, phosphocholine, and glycerophosphocholine; TMA is typically elevated in malignancies, including malignant soft tissue tumors.…”
Section: Quantitative Mri Biomarkersmentioning
confidence: 99%
“…MRS is a technique that is used to noninvasively detect and distinguish metabolite activity in a tissue of interest, such as a soft tissue tumor, based on the intrinsic resonant frequencies of various metabolites, and analyze its biochemical composition . MRS enables the detection of metabolic markers of malignancy, including the trimethyl aluminium (TMA) compounds, which present as a composite spectral resonance consisting of free choline, phosphocholine, and glycerophosphocholine; TMA is typically elevated in malignancies, including malignant soft tissue tumors.…”
Section: Quantitative Mri Biomarkersmentioning
confidence: 99%
“…Most previous studies, although including some soft‐tissue tumors, have demonstrated a high tendency for choline peaks to be present in malignant osseous tumors (Fig. ).…”
Section: Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 90%
“…A choline peak tends to be found in GCT with aggressive radiographic features like cortical breaches and associated soft‐tissue masses . Some malignant osseous tumors can fail to show a choline peak . Slow‐growing low‐grade chondrosarcoma is representative; in one report only one of six cases (16.7%) had a choline peak (Fig.…”
Section: Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 97%
See 2 more Smart Citations